Geophysical and Remote Sensing Data for Delineating Structural Elements at El Hammam Area, Northern Part of Western Desert, Egypt - Araffa, S. A. S.; Mohamaden, M. I.; Abu-Hashesh, M. F.; Galal, A. N. H.; Takey, M. S.; Hassan, N. M. (Geotectonics, 2024)
El-Hammam area is situated along the northwest coastal region of Egypt, which is a tight strip of ground between the Mediterranean and the vast deserts outside of the delta agricultural region on the west. A digital elevation model (DEM) and Landsat-8 image with a 30 m resolution were used. Also, the data were utilized in the geomorphological analysis and interpretations of the geology of the El Hammam area. The processed Landsat ETM + satellite imageries were used to interpret and construct the geological map. The digital data of the DEM has been utilized to extract the structural lineaments map. The main geomorphic properties of the El Hammam area were delineated by the geomorphological analysis. Gravity data are utilized to determine the subsurface features (faults and basins) and the depth of the basement, where are used processing and filtering techniques to outline the dominant structure. The interpretation of the gravity data reveals that directions of the major structures are aligned in NW‒SE and NE‒SW whereas the small structures are alignment in E‒W, WNW‒ESE, ENE‒WSW, NNE‒SSW, N‒S, and NNW–SSE directions. The findings of depth in order to estimate the basement rocks by 2D and 3D modeling ranges from 1254 m at the SW and western parts to 5650 m at the SE and eastern parts of the study area.